Meat, eggs, dairy products, and risk of breast cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. - Pala, V; Krogh, V; Berrino, F; Sieri, S; Grioni, S; Tjønneland, A; Olsen, A; Jakobsen, M; Overvad, K; Clavel-Chapelon, F; Boutron-Ruault, M; Romieu, I; et al. (2009)
BACKGROUND: A Western diet is associated with breast cancer risk. OBJECTIVE: We investigated the relation of meat, egg, and dairy product consumption with breast cancer risk by using data from the European Prospective Investigation into Cancer and Nutrition (EPIC). DESIGN: Between 1992 and 2003, information on diet was collected from 319,826 women. Disease hazard ratios were estimated with multivariate Cox proportional hazard models. RESULTS: Breast cancer cases (n = 7119) were observed during 8.8 y (median) of follow-up. No consistent association was found between breast cancer risk and the consumption of any of the food groups under study, when analyzed by both categorical and continuous exposure variable models. High processed meat consumption was associated with a modest increase in breast cancer risk in the categorical model (hazard ratio: 1.10; 95% CI: 1.00, 1.20; highest compared with lowest quintile: P for trend = 0.07). Subgroup analyses suggested an association with butter consumption, limited to premenopausal women (hazard ratio: 1.28; 95% CI: 1.06, 1.53; highest compared with lowest quintile: P for trend = 0.21). Between-country heterogeneity was found for red meat (Q statistic = 18.03; P = 0.05) and was significantly explained (P = 0.023) by the proportion of meat cooked at high temperature. CONCLUSIONS: We have not consistently identified intakes of meat, eggs, or dairy products as risk factors for breast cancer. Future studies should investigate the possible role of high-temperature cooking in the relation of red meat intake with breast cancer risk.